Mortality due to cancer of the uterine cervix in the state of Minas Gerais, Brazil, 1980-2005: period and cohort analysis Mortalidade por câncer de colo de útero no Estado de Minas Gerais, Brasil, 1980-2005: análise de período e coorte - Christiane Maria Meurer Alves; Ronaldo Rocha Bastos; Maximiliano Ribeiro Guerra (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
This study identifies the period and cohort effects on the decreasing mortality trend of cancer of the uterine cervix and of the uterus, part unspecified, in the state of Minas Gerais, Brazil, during the period 1980-2005. 11,243 cases were included. A non-parametric method was used to calculate Z statistics and p-values. The cohorts were assessed one by one and also in blocks of three, so as to allow for a larger number of comparisons to be made. Greater than expected mortality reduction was observed for the cohort blocks of women born in 1913-1920; 1927-1936; 1937-1946; 1949-1956; 1963-1970; and 1969-1976. For the 1901-1908 and 1921-1928 cohort blocks a smaller than expected mortality decrease was found. As for period effect, we found a greater than expected reduction for the 2000-2001 period, in comparison with the previous one. The study suggests the existence of a significant cohort effect on mortality due to cancer of the uterine cervix in the study population, and such results have been placed in their social and political contexts. Buscou-se identificar os efeitos período e coorte na tendência de mortalidade por câncer de colo de útero e útero porção não especificada, no Estado de Minas Gerais, Brasil, no período de 1980-2005. Foram incluídos 11.243 casos. Utilizou-se método não paramétrico para o cálculo da estatística Z e valor de p. As coortes foram avaliadas uma a uma e em blocos de três, para possibilitar o aumento do número de comparações. Observou-se redução da mortalidade maior que a esperada para os blocos de coortes das mulheres nascidas de 1913-1920; 1927-1936; 1937-1946; 1949-1956; 1963-1970; 1969-1976. Para os blocos de coortes de 1901-1908 e 1921-1928, encontrou-se redução da mortalidade menor que a esperada. No que se refere ao efeito período, foi evidenciada uma redução maior que a esperada para o período de 2000-2001, quando comparado ao anterior. O estudo sugere a existência do efeito coorte significativo sobre a mortalidade por câncer de colo de útero na população estudada, os resultados foram confrontados com o contexto social e político.